2020
DOI: 10.1039/d0ob00617c
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of the trichostatin gene cluster and functional characterization ofN-methyltransferase TsnB8

Abstract: N-Methyltransferase TsnB8 was demonstrated to catalyze successive methyltransfer reactions in the biosynthesis of trichostatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…23−25 The olefin group of the released intermediate is then reduced by an unknown enol reductase (ER), followed by two methyl transfer reactions catalyzed by N-methyltransferase (tsnB8), which convert the formed intermediate to 2 and subsequently to 1. 4 In the second case, 1 and 2 could be formed by the enzymatic degradation of TSA. This hypothesis is based on the isolation of dehydroxytrichostatin A (8), which has a short branched carbon chain compared to TSA, and the results of the previous study on mice, 20 suggesting that 1 is produced due to biodegradation of TSA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…23−25 The olefin group of the released intermediate is then reduced by an unknown enol reductase (ER), followed by two methyl transfer reactions catalyzed by N-methyltransferase (tsnB8), which convert the formed intermediate to 2 and subsequently to 1. 4 In the second case, 1 and 2 could be formed by the enzymatic degradation of TSA. This hypothesis is based on the isolation of dehydroxytrichostatin A (8), which has a short branched carbon chain compared to TSA, and the results of the previous study on mice, 20 suggesting that 1 is produced due to biodegradation of TSA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additional modification genes were also found to be involved in the formation of trichostatin analogues. 3,4 In this study, we found that, in addition to compounds 1 and 2, Streptomyces sp. 13F051 also produces trichostatin analogues 3−10, which bear an additional propionate unit in the branched carbon chain.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations